Neonatal ventilation with a manikin model and two novel PEEP valves without an external gas source. Issue 3 (29th August 2016) - Thallinger, Monica; Ersdal, Hege Langli; Morley, Colin; Purington, Carolyn; Gomo, Øystein; Mduma, Estomih; Eilevstjønn, Joar; Størdal, Ketil
Abstract : Objective: Positive end expiratory pressure (PEEP) is beneficial when ventilating preterm newborns. The aim was to study whether inexperienced providers were able to generate PEEP during simulated neonatal ventilation, using two novel prototype PEEP valves, on a self-inflating bag without an external gas source. Design: Forty-six nursing students in Tanzania were trained in ventilation with a new Laerdal Upright resuscitator and mask on a NeoNatalie manikin with a newborn resuscitation monitor. Ventilation was studied with and without PEEP valve 1 (anticipated level 4–5 cm H2 O) and with and without PEEP valve 2 (anticipated level 9–10 cm H2 O) in random order for normal and low 'lung' compliance. The PEEP valves were concave silicone valves with a small slit that would open to let expiratory air out. Results: Mean PEEP with PEEP1 was 4.4 cm H2 O (SD 2.2) and with PEEP2 was 4.9 cm H2 O (SD 3.1). PEEP ≥4 cm H2 O was generated with 70% of inflations with PEEP1 and 65% with PEEP2. Mean airway pressure was 16.3 cm H2 O with both PEEP valves compared with 14.2 without PEEP (p<0.001). Mean mask leak was similar with and without PEEP (48% with PEEP1, 58% with PEEP2, 55% without PEEP). Mask leak and PEEP were inversely correlated. Findings with normal and low 'lung' compliance were similar. Conclusions: PEEP between 4 cm H2 O and 5 cm H2 O was achieved when ventilating a neonatal manikin using a self-inflating bag and novel PEEP valves. Valves that can generate PEEP without external gas sources may aid resuscitation in resource-limited settings.